From Traditional Records to Standardized Reporting: The Impact of PSAK 45 and PSAK 109 on Mosque Financial Transparency - Ahmad Hazmi Erde; Nurlaila Nurlaila (Program Pascasarjana UIN Sumatera Utara, 2025)
This study examines the reconstruction of mosque financial reporting systems in Indonesia through the application of PSAK 45 and PSAK 109 in response to persistent governance challenges. Despite managing substantial public funds, many mosques continue to rely on manual, non-standardized bookkeeping practices that limit transparency, auditability, and accountability. National evidence indicates that more than 70% of mosques have not implemented formal accounting standards, resulting in inconsistent reporting and weak oversight. Using a qualitative literature review, this study synthesizes empirical findings, regulatory frameworks, and theoretical perspectives to evaluate the relevance and applicability of PSAK 45 for nonprofit financial reporting and PSAK 109 for managing zakat, infak, and sadaqah funds. The review reveals that both standards provide structured mechanisms for fund classification, disclosure, and documentation, allowing mosques to transition from informal cash-based reports to comprehensive, auditable statements. However, implementation remains constrained by limited financial literacy, lack of regulatory enforcement, and cultural perceptions of informal mosque governance. The study proposes an integrated framework emphasizing capacity building, standardized reporting templates, and strengthened internal controls. The findings highlight that adopting PSAK 45 and PSAK 109 offers significant opportunities to enhance institutional credibility, donor trust, and long-term financial sustainability. This research underscores the urgent need for standardized accounting practices to modernize mosque financial governance and strengthen public accountability